Development of a new index of strength in adults with intellectual and developmental disabilities - Merchán-Baeza, Jose Antonio; Pérez-Cruzado, David; González-Sánchez, Manuel; Cuesta-Vargas, Antonio (Taylor and Francis, 2019)
Background: Given the increase in the prevalence of muscular strength problems in people with intellectual and developmental disability and the potentially serious consequences for their day-to-day life, there is a need for comprehensive evaluations of strength. Aims: To design a new index of the muscular strength of people with intellectual and developmental disability using principal components analysis. Methods and procedures: The sample consisted of 978 individuals with intellectual and developmental disability, 637 men and 341 women, with a mean age of 34.8 years (±11.2) who were recruited from the European Special Olympics Games. All participants were measured with the following functional tests: timed stand test, partial sit-up test, seated pushup and handgrip test. Outcomes and results: Data was analyzed using principal components analysis with Oblimin rotation and Kaiser normalization. The Component Plot and Rotated Space indicated that a one-factor solution was optimal. The principal component analysis revealed a satisfactory percentage of total variance explained. Conclusions: Based on the data analyzed above we believe that the strength index developed in this study could help to facilitate the assessment and follow-up of people with intellectual and developmental disability in the clinical setting, because it offers a broad measure of an individual’s muscular response generated to the various stimuli presented by the evaluator. In addition, because it is economical, and easy and quick to administer, this index could easily be applied in clinical and research settings.
Keywords: Condición física; Strength; fitness condition; intellectual disability; muscular strength; physical fitness